Conflict Resolution Approach in Social Studies Learning as an Educational Instrument to Cultivate Nationalistic Values In Border Schools - Benu, Asti Yunita; Wiyanarti, Erlina; Sapriya, Sapriya; Ruhimat, Mamat (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
Schools in the Indonesia-Timor Leste border region, including SMP Negeri 2 Atambua, face unique challenges in instilling national values in students living in a diverse social and cultural environment. By implementing a conflict resolution approach in social studies, teachers can transform the learning process into an educational tool to foster national awareness and tolerance among students living in the border region. This study aims to determine and describe the application of the conflict resolution approach in social studies learning as an educational instrument to instill nationalist values in schools in the Indonesia-Timor Leste border area. The location of the study was at SMP Negeri 2 Atambua, with research subjects including teachers, students, principals, and other related parties. The method used was a qualitative case study, through in-depth interviews, participatory observation, and documentation studies. The results of the study indicate that the application of the conflict resolution approach in social studies learning can create a harmonious learning atmosphere and reduce social tensions between students, while at the same time instilling nationalist values related to Indonesian history, state symbols, and the importance of maintaining the integrity of the nation. However, there are challenges faced, such as limited resources, facilities, and teacher training, as well as complex socio-cultural dynamics in the border area. The implementation of this approach is expected to be a strategic instrument in strengthening the nationalist character in the border area.